Strategy for Developing Islamic Education in an Effort to Anticipate the Development of Science and Technology - Bakti, Surya; Yani, Ade Najira; Bilbina, Alzaiti; Raisha, Nazwa; Syahrapi, Ridho Bayu; Nadila, Arwina (Holistic Science, 2025)
This study aims to analyze strategies for developing Islamic education to anticipate the advancement of science and technology (IPTEK) in the digital era. The research employs a descriptive qualitative method with data collected through interviews, literature review, and observations. The findings reveal that the development of Islamic education requires a curriculum transformation integrating Islamic values with technology, improving teachers' digital literacy competencies, and fostering collaboration between educational institutions and the technology industry. The primary challenges in implementing these strategies include limited technological infrastructure, resistance to change, and low technological competence among educators. Proposed solutions include providing adequate infrastructure, implementing continuous training programs for educators, and strengthening policies to support technology-based educational transformation. With the right strategies, Islamic education is expected to produce a generation of Muslims who are intelligent, competitive, and possess strong moral character amidst rapid technological advancements.